2009
DOI: 10.1158/0008-5472.can-09-0458
|View full text |Cite
|
Sign up to set email alerts
|

Azacytidine Inhibits RNA Methylation at DNMT2 Target Sites in Human Cancer Cell Lines

Abstract: The cytosine analogues azacytidine and decitabine are currently being developed as drugs for epigenetic cancer therapy. Although various studies have shown that both drugs are effective in inhibiting DNA methylation, it has also become clear that their mode of action is not limited to DNA demethylation. Because azacytidine is a ribonucleoside, the primary target of this drug may be cellular RNA rather than DNA. We have now analyzed the possibility that azacytidine inhibits the RNA methyltransferase DNMT2. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(139 citation statements)
references
References 26 publications
6
131
0
2
Order By: Relevance
“…The induced responses may not be a general stress phenomenon as they do not occur with carboplatin, a cytotoxic agent commonly used in EOC treatment (Figure 1b). Aza and Dac incorporate into DNA, inhibiting 3 DNA methyltransferases (Schaefer et al, 2009), but Aza also incorporates into RNA, inhibiting the RNA methyltransferase DNMT2. Aza thus can demethylate RNA, and unmethylated RNA may activate TLR3 and the interferon response (Kariko et al, 2005).…”
Section: Dnmtis Trigger Viral Defense and Type I Interferon Signalingmentioning
confidence: 99%
“…The induced responses may not be a general stress phenomenon as they do not occur with carboplatin, a cytotoxic agent commonly used in EOC treatment (Figure 1b). Aza and Dac incorporate into DNA, inhibiting 3 DNA methyltransferases (Schaefer et al, 2009), but Aza also incorporates into RNA, inhibiting the RNA methyltransferase DNMT2. Aza thus can demethylate RNA, and unmethylated RNA may activate TLR3 and the interferon response (Kariko et al, 2005).…”
Section: Dnmtis Trigger Viral Defense and Type I Interferon Signalingmentioning
confidence: 99%
“…60 Indeed, Lyko and colleagues have shown that 5-azacitidine is incorporated into RNA species and results in hypomethylation of transfer RNA. 61 Although dozens of covalently modified RNA species are recognized currently, studying how 5-azacitidine changes RNA species is technically challenging, and we suggest this area is ripe for reexamination. 5-azacitidine-modified RNA could have an even greater impact than in DNA.…”
Section: The True Mechanism Of Action Of the Hypomethylating Agentsmentioning
confidence: 98%
“…5 Furthermore, 5-azacytidine inhibits protein production by being incorporated into RNA and interrupting its performance. 6,7 Although a few investigations have illustrated the effectiveness of experiments, 8,9 most clinical trials of the effects of 5-azacytidine on solid tumors are disappointing. 10 Due to its short half-life, 5-azacytidine is unable to permeate solid tumors and remain long enough to affect cancer cells.…”
Section: -Azacytidine Was First Synthesized In 1963mentioning
confidence: 99%